Pengaruh Literasi Digital terhadap Intensi Kewirausahaan Digital Siswa Sekolah Menengah Kejuruan (SMK) - Kusumaningrum, Alifah; Kusnendi, Kusnendi (Jurusan PIPS FKIP UMMY Solok, 2022)
This study aims to determine the effect of digital literacy and entrepreneurship education on digital entrepreneurship intentions. The research method used is an explanatory survey using a questionnaire as data collection. The population in this study were vocational school students majoring in for the 2021/2022 academic year and a sample of 200 students was taken using a simple random sampling technique. The data analysis technique used is multiple linear regression analysis. The results of the study indicate that digital literacy affects students' digital entrepreneurship intentions in senior high schools (SMK). Based on the significance value: the coefficients table obtained a significant value of 0.000 < 0.05, so it can be concluded that the economic digital literacy variable has an effect on the variables of digital entrepreneurship intentions. Based on the t value: it is known that the tcount value is 34,881 > 1,97, so it can be concluded that the economic digital literacy variable affects the digital entrepreneurship intention on Vocational High School.